The Effect of the Talking Chips Cooperative Model Based on the Quiz Team Strategy on Interest and Learning Outcomes - Senta; Enawaty, Eny; Harun, Andi Ifriany (Universitas Pendidikan Mandalika, 2025)
The Talking Chips learning model is a cooperative approach that uses cards as a tool to regulate speaking turns. Meanwhile, the Quiz Team strategy aims to improve group cooperation through fun activities. This study aims to determine the effect of applying the Talking Chips model based on the Quiz Team strategy on students' interest and learning outcomes. The research was conducted with a quantitative approach using a quasi-experimental method and a post-test only control group design. The study was conducted at SMPN 26 Pontianak City in the even semester of the 2024/2025 academic year with a sample of two eighth grade classes with equal academic abilities. The experimental class received learning using the Talking Chips model based on the Quiz Team strategy, while the control class used conventional learning. The research instruments consisted of a learning interest questionnaire and a post-test learning outcome test.The results showed that the average learning outcome score of students in the experimental class (68.23) was higher than that of the control class (60.16), with a significant difference based on the Mann-Whitney test (Sig. 0.046). The Effect Size value of learning outcomes was 0.52, indicating that the learning model had a moderate effect on learning outcomes. In addition, in terms of learning interest, the experimental class obtained a “Very High” category with an average of 91.8%, while the control class was in the “Fair” category with an average of 69.4%. The t-test showed a significant difference (Sig. 0.000) with an Effect Size value of 2.02, which means that the learning model has a very large effect on learning interest. This study combines the Talking Chips model with the Quiz Team strategy as a cooperative learning approach that has been proven effective in increasing student interest and learning outcomes simultaneously.